Individual precocity, temporal persistence, and task-specialization of hygienic bees from selected colonies of apis mellifera - Scannapieco, Alejandra Carla (2016)
Hygienic behaviour is a complex trait that gives Apis mellifera L. resistance against brood diseases. Variability in the expression of hygienic behaviour is evidenced at the colonylevel and is explained by the proportion and propensity of individual worker bees that engage in hygienic activities. We investigated the temporal performance and the dynamics of task-specialisation of individual bees over time, both in selected hygienic (H) and non-hygienic (NH) colonies. Then we evaluated the impact of these behavioural aspects on the colony performance. Bees that perform hygienic behaviour (hygienic bees) in our H colonies were more persistent in the hygienic activities throughout the days of the investigation. Such bees were more efficient in the removal of pin-killed brood than hygienic bees in the NH colonies. Hygienic bees in the H colonies were also specialist in the sub-tasks involved in the detection of odour stimulus from dead brood and continued to perform these activities throughout the days of the investigation (temporal persistence). Age-distribution of hygienic bees in the H colonies was asymmetrical, with a larger proportion of these bees performing hygienic activities early in life. At a colony-level, H showed higher efficiency compared to the NH colonies. The present results highlight the fact that individual behaviour may influence the collective dynamics of the hygienic behaviour in honeybee colonies. The results also note that the selection for highly hygienic colonies would result in changes in individual bees that improve the performance of the behaviour at the colony level. The relevance of task-partitioning and age-specialisation of hygienic bees on social immunity is discussed.